2008
DOI: 10.1124/jpet.108.142992
|View full text |Cite
|
Sign up to set email alerts
|

Chymase-Dependent Conversion of Big Endothelin-1 in the Mouse in Vivo

Abstract: The aim of this study was to identify the role of chymase in the conversion of exogenously administered Big endothelin-1 in the mouse in vivo. Real-time polymerase chain reaction analysis detected mRNA of mucosal mast cell chymases 4 and 5, endothelin-converting enzyme 1a, and neutral endopeptidase 24.11 in pulmonary, cardiac, and aorta homogenates derived from C57BL/6J mice, with the latter tissue expressing the highest levels of both chymase isoforms. Furthermore, hydrolysis of a fluorogenic peptide substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…These results are concordant with previously reported data from our laboratory showing that a chymase inhibitor, Suc-Val-Pro-Phe P (OPh) 2 , inhibited by over 60% the pressor response of Big ET-1 and reduced the plasma level increases of ET-1 by close to 90% in WT mice in vivo (Simard et al, 2009). Although this does not prove conclusively of a more important role of chymase versus ECE .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are concordant with previously reported data from our laboratory showing that a chymase inhibitor, Suc-Val-Pro-Phe P (OPh) 2 , inhibited by over 60% the pressor response of Big ET-1 and reduced the plasma level increases of ET-1 by close to 90% in WT mice in vivo (Simard et al, 2009). Although this does not prove conclusively of a more important role of chymase versus ECE .…”
Section: Discussionsupporting
confidence: 81%
“…Specific ECE inhibition with CGS 35066 reduced the pressor response to Big ET-1 in a similar fashion in both groups and further inhibited the residual response to the 38 amino acid precursor in mMCP-4(2/2) mice, whereas both groups responded equally to ET-1 (1-31) administration. Our group previously showed the dual contribution of both chymase and NEP in the in vivo conversion of Big-ET-1 to ET-1 in WT mice (Simard et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mechanisms other than the renin-angiotensin-aldosterone system, such as endothelin, should be considered because mouse or human chymase can process big endothelin to active endothelin-(1-21) (39,43). In addition, it has been previously reported that HS loading in Dahl saltsensitive rats increases blood pressure and renal endothelin expression, which are reversed by an endothelin receptor blocker (17).…”
mentioning
confidence: 99%
“…In a separate group of vessels, the endothelium was mechanically removed, and vessels were subsequently exposed to ET (10 Ϫ9 to 10 Ϫ7 M) (n ϭ 6) and to Big ET (10 Ϫ8 to 10 Ϫ6 M) in the absence (n ϭ 7) and presence (n ϭ 6) of 8-Br-cGMP (100 M). Based on in vivo (7) and in vitro (35,43) observations, we selected a higher dose range of Big ET than ET to achieve similar vasoconstrictor responses. Big ET has no direct vasomotor effect (34), so that the Big ET-induced vasoconstriction reflects the conversion from Big ET to vasoactive ET (7).…”
Section: Myograph Studies Of Isolated Coronary Small Arteriesmentioning
confidence: 99%